DEVELOPMENT OF SCRATCH-BASED EDUCATION GAME TO TRAIN CRITICAL THINKING SKILLS ON HUMAN MOVEMENT SYSTEM MATERIAL - Annisa Nurfadhilah; Prasetyo Listiaji (Universitas Bhinneka PGRI, 2024)
Learning in the 21st century requires students to have critical thinking skills. However, based on the result of previous research and observations at MTs Al Uswah Bergas it is known that students' critical thinking skills are still at a low level. Scratch-based Edugame is identified as a potential learning media to train students' critical thinking abilities. This study aims to determine the validity of Scratch-based Edugame, analyze the level of students' critical thinking skills after using Scratch-based Edugame, and also determine student responses after using Scratch-based Edugame. This research follows the Research and Development (RD) method with ADDIE model. The validation results indicate that the Edugame learning media is valid, with a Vcount of 0.91. After using the Edugame, 36.7% students achieved critical thinking skills in the high category and 63.3% students demonstrated critical thinking skills in the very high category. Furthermore, students responded positively to the Scratch-based Edugame, with an average student response rating of 89.6%. Based on the results, the Scratch-based Edugame learning media is found to be valid and effective to train students’ critical thinking skills, meanwhile, the overall student response to this Edugame learning media was very good.